Make carbon footprints available – And it is not just one value - Ari Nissinen; Jyri Seppälä; Tero Heinonen (Cleaner Logistics and Supply Chain)
The carbon footprint (CF) should finally have a role in the decision-making of manufacturing companies, retailers, public procurers and consumers. We consider that more systematic approaches are urgently needed for collecting, storing and presenting carbon footprint information. The key issue from the standpoint of reliability and comparability is to recognise how each CF was determined and how it has been verified. Global Trade Item Number (GTIN) and the connected barcode symbol can be used to identify products. We propose that the presented framework can help to build databases which are easy to use for the manufacturers, retailers and various service providers and which can increase the production and usability of CF information.